2010
DOI: 10.3109/02699051003670882
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of heterogeneity in neurocognitive profiles associated with traumatic brain injury

Abstract: The outcome of traumatic brain injury is heterogeneous and mainly associated with demographic considerations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 15 publications
1
13
1
Order By: Relevance
“…The primary limitations of this current study are related to the small group size limiting generalizability of this study. However, despite the small patient group size and the known heterogeneity of TBI ( Goldstein et al, 2010 , León-Carrión et al, 2012 ), we found a strong and significant correlation of executive attention with its associated electrophysiological patterns extracted using PCA. Most importantly, the robustness of our results is further validated by a similar PC extracted from an out-of-sample group of control subjects only (Supplementary Fig.…”
Section: Discussioncontrasting
confidence: 53%
“…The primary limitations of this current study are related to the small group size limiting generalizability of this study. However, despite the small patient group size and the known heterogeneity of TBI ( Goldstein et al, 2010 , León-Carrión et al, 2012 ), we found a strong and significant correlation of executive attention with its associated electrophysiological patterns extracted using PCA. Most importantly, the robustness of our results is further validated by a similar PC extracted from an out-of-sample group of control subjects only (Supplementary Fig.…”
Section: Discussioncontrasting
confidence: 53%
“…Furthermore, individuals with TBI frequently have comorbid psychiatric conditions such as depression and posttraumatic stress disorder (PTSD) (Ashman et al., 2004; Hibbard, Uysal, Kepler, Bogdany, & Silver, 1998; van Reekum, Bolago, Finlayson, Garner, & Links, 1996), and this comorbidity affects the brain and neuropsychological performance (Han, Chapman, & Krawczyk, 2015; Hudak, Hynan, Harper, & Diaz‐Arrastia, 2012; Hudak et al., 2011; Lindemer, Salat, Leritz, McGlinchey, & Milberg, 2013; Lopez et al., 2016; Spielberg, McGlinchey, Milberg, & Salat, 2015), exacerbating the heterogeneity challenge. Accordingly, behavioral performance of individuals with TBI, measured by neuropsychological tests, is heterogeneous (Goldstein, Allen, & Caponigro, 2010; Tellier et al., 2009; Thaler et al., 2013). In the context of rehabilitation, heterogeneity is further increased by variation in responses to rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…25 The Wechsler Intelligence Scale (WIS) has a complex structure with verbal and operational subtests and can provide three IQ scores and multiple subtest scores at the same time. 26 The Minnesota Multiphasic Personality Inventory (MMPI) is currently one of the most commonly used tests in the world using the questionnaire test method consisting of a total of 566 questions in the form of selfreporting. 27 Further, there are some methods, such as nerve electrophysiological examination, 28 transcranial Doppler ultrasound imaging (TCD), 29 and magnetic resonance imaging (MRI) 7 that are also performed for evaluating changes between POCD and non-POCD patients.…”
Section: Diagnosis Of Pocdmentioning
confidence: 99%